Treatment of Combined Freckles with Chloasma Using Q-Switched 1064 nm Laser - Han Zheng; Gang Qiao; Yong Zhang (International Journal of Clinical Practice)
Objective. The present study observed the therapeutic effect and possible side effects of Q-switch 1064-nm laser with large-spot and low-energy technology in the treatment of patients with combined freckles and chloasma. Methods. A Q1064-nm laser with a large-spot diameter of 6–8 mm, energy level of 2.0–3.3 J/cm2, frequency of 10 Hz, and pulse width of 10 ns was employed for the treatment. Each patient underwent treatment 10–15 times, with an interval of 10–15 days each time. Facial care was administered before and after treatment; attention was paid to cleaning and moisturizing, avoiding light, and using sunscreens strictly. The therapeutic effects were observed and evaluated. Results. Freckles basically subsided (effective rate = 100%) and chloasma faded (effective rate = 39.4%). Furthermore, whitening and delicacy improvement were observed in the surrounding normal skin area. After laser treatment, confocal laser scanning microscopy revealed a large number of melanin particles in the upper part of the granular layer. Moreover, the amount of melanin in the middle and lower parts of the basal layer and spinous layer was significantly decreased. None of the patients developed postinflammatory pigmentation. Conclusion. In the treatment of freckles with chloasma, Q 1064-nm laser large-spot, low-energy technology not only removed freckles and faded chloasma but, most importantly, also reduced the incidence of postinflammatory pigmentation and improved patient satisfaction. This provided new methods and ideas for freckle laser treatment.